Distinctive Growth and Transcriptional Changes of the Diatom Seminavis robusta in Response to Quorum Sensing Related Compounds - Stock, Frederike; Bilcke, Gust; De Decker, Sam; Osuna-Cruz, Cristina Maria; Van den Berge, Koen; Vancaester, Emmelien; De Veylder, Lieven; Vandepoele, Klaas; Mangelinckx, Sven; Vyverman, Wim (Frontiers in Microbiology, 2020)
In aquatic habitats, diatoms are frequently found in association with Proteobacteria, many members of which employ cell-to-cell communication via N-acyl homoserine lactones (AHLs). It has been suggested that diatoms could distinguish between beneficial and algicidal bacteria in their surroundings by sensing AHLs. Although some microalgae can interfere with AHL signaling, e.g. by releasing AHL mimics or degrading them, molecular responses to AHLs in microalgae are still unclear. Therefore, we tested the effects of short-chained AHLs, i.e. N-hexanoyl homoserine lactone (C6-HSL), N-3-hydroxyhexanoyl homoserine lactone (OH-C6-HSL) and N-3-oxohexanoyl homoserine lactone (oxo-C6-HSL) and long-chained AHLs, i.e. N-tetradecanoyl homoserine lactone (C14-HSL), N-3-hydroxytetradecanoyl homoserine lactone (OH-C14-HSL) and N-3-oxotetradecanoyl homoserine lactone (oxo-C14-HSL), on growth of the benthic diatom Seminavis robusta. All tested short-chained AHLs did not affect diatom growth, while long-chained AHLs promoted (C14-HSL) or inhibited (OH-C14-HSL and oxo-C14-HSL) growth. To investigate the physiological effects of these long-chained AHLs in more detail, an RNA-seq experiment was performed during which S. robusta was treated with the growth-promoting C14-HSL and the growth-inhibiting oxo-C14-HSL. One tetramic acid was also tested (TA14), a structural rearrangement product of oxo-C14-HSL, which also induced growth inhibition in S. robusta. After three days of treatment, analysis revealed that 3,410 genes were differentially expressed in response to at least one of the compounds. In the treatment with the growth-promoting C14-HSL many genes involved in intracellular signaling were upregulated. On the other hand, exposure to growth-inhibiting oxo-C14-HSL and TA14 triggered a switch in lipid metabolism towards increased fatty acid degradation. In addition, oxo-C14-HSL led to downregulation of cell cycle genes, which is in agreement with the stagnation of cell growth in this treatment. Combined, our results indicate that bacterial signaling molecules with high structural similarity induce contrasting physiological responses in S. robusta.